Letramento multimodal de uma criança surda com implante coclear - Pires, Thereza Sophia Jácome (2018)
Linguistic studies have demonstrated a knowledge interface with other areas, for example, Speech Therapy. Regarding the acquisition and development of oral and written language, both fields demonstrate interest in researching and analyzing aspects such as the typical and pathological patterns that exert influence in the language in general, as in cases related to deafness. The Cochlear Implant aims to increase the physiological perception of sounds and can be used by people with deafness with severe-deep hearing loss. According to (BELLOTTI, 2014; CRUZ, 2016), the written language acquisition of these children occurs through oral language or sign language and, moreover, the period of hearing deprivation plays a primordial role in relation to the language collection in Brazilian Portuguese (BP). In this way, this study was designed to analyze the appropriation of the written language system of a deaf child with cochlear implant, from the point of view of literacy, from a perspective of language as a multimodal instance. During the structuring of the thesis, the following theoretical bases were consulted Mcneill (2000), Cavalcante (1994, 1999, 2010), Brandão (2012), Faria (2011), Ávilla-nobrega (2015), Soares (2018) as a contribution to our understanding of multimodality language Morais (2012), Sciliar-Cabral (1999), Queiroz (2008), Dionísio (2011) to discuss issues related to literacy and multimodality. As a data collection procedure, the speech-language pathology sessions were filmed during weekly consultations, in a clinic in the city of João Pessoa, from the moment the Informed Consent was signed by the responsible person. The research had the participation of a child with congenital deafness of the female, having been implanted at the age of 4 years, and who had 09 years and 06 months at the beginning of the collection. For the analysis of the data, the ELAN software was used in order to qualitatively describe the linguistic relations constructed from phonoaudiological intervention. The results of the research indicate that phonoaudiological intervention, based on the premise of multimodality, where gesture and speech co-operate in the child’s linguistic development together with literacy practices to acquire the written code, favored the Brazilian Portuguese (BP) written by the child using a cochlear implant, since it was possible to verify a development of reading and an increase in writing productions. In addition, we observed movements that represented the writing in the air during the literacy sessions, at the moment when the implanted reflected on the writing of words about which still had no mastery. Therefore, the study found that only the activation of C.I. and the exposure to oral language are insufficient to acquire written Brazilian Portuguese (BP), as it is necessary to expose the alphabetical writing system associated with a planning of activities that develop predictive skills for reading.